2022
DOI: 10.3389/fonc.2022.826058
|View full text |Cite
|
Sign up to set email alerts
|

CT-Derived Body Composition Values and Complications After Pneumonectomy in Lung Cancer Patients: Time for a Sex-Related Analysis?

Abstract: PurposeThis study aimed to assess if CT-derived body composition values and clinical characteristics are associated with the risk of postsurgical complications in men and women who underwent pneumonectomy for lung cancer.Materials and MethodsPatients who underwent pneumonectomy between 2004 and 2008 were selected. The ethics committee approved this retrospective study with waiver of informed content. Main clinical data collected were sex, age, weight and height to calculate body mass index (BMI), albumin, C-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Besides surveying CT-based visceral fat measurements and associating them with some important demographic and pathological variables in NSCLC, our study demonstrates the practicability and encourages the use of routine CT data to include visceral obesity as an examined factor in lung cancer research. Visceral adiposity is also of relevance in immediate clinical care of lung cancer for its influence on pulmonary function [ 30 ] and outcomes such as post-pneumonectomy complications [ 31 ] and radiation pneumonitis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides surveying CT-based visceral fat measurements and associating them with some important demographic and pathological variables in NSCLC, our study demonstrates the practicability and encourages the use of routine CT data to include visceral obesity as an examined factor in lung cancer research. Visceral adiposity is also of relevance in immediate clinical care of lung cancer for its influence on pulmonary function [ 30 ] and outcomes such as post-pneumonectomy complications [ 31 ] and radiation pneumonitis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also wanted to point out the practicability of measuring visceral obesity by examining routinely collected radiological data using facile software-based methods. CT image data and workflow that are used for visceral obesity examination can be simultaneously used to measure other body composition features, such as skeletal muscle area [ 31 ], which may also have biomarker value in clinical care and research. With advances in image analysis, including incorporation of deep-learning-based approaches [ 40 ], it is possible that in the very near future, visceral obesity metrics will be automatically and accurately generated within radiology viewer applications themselves.…”
Section: Discussionmentioning
confidence: 99%
“…11 Computed tomography (CT) is considered the gold standard for assessing body composition, allowing non-invasive and objective simultaneous quantification of the amount of skeletal muscle and adipose tissue at the desired anatomical level. 12 Chest CT is routinely performed in NSCLC patients during the initial diagnosis and follow-up assessment and may be the best option for the regular assessment of thoracic skeletal muscle and fat. 13 Previous studies have shown that sarcopenia, which is indicated by reduced pectoralis muscle mass on CT, is significantly associated with poor OS in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Body composition assessment may include evaluation of muscle mass by skeletal muscle area (SMA) and skeletal muscle index (SMI), as well as assessment of fat distribution by subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). Body composition has been shown to correlate with prognosis in many cancer subtypes, including ovarian ( 6 ), lung ( 7 ), bladder ( 8 ) and pancreatic malignancies ( 9 ). Furthermore, in some cancer types, sarcopenia increases the toxicity of chemotherapy ( 10 , 11 ), likely because drug dosing is largely based on the body surface area, that takes into account only the patient’s height and weight but ignores the relative quantity and distribution of muscle and fat.…”
Section: Introductionmentioning
confidence: 99%